The consideration of building maintenance at design stage in public buildings: The current scenario in Malaysia. Issue 13 (7th October 2019) - Khalid, Ellemy Iskandar; Abdullah, Shardy; Hanafi, Mohd Hanizun; Said, Shahrul Yani; Hasim, Mohamad Sufian
Abstract : Purpose: Effective building maintenance management is vital for reducing the impact of building defects and costly building maintenance work. Such practice significantly contributes to the public sector in terms of cost reduction, improved effectiveness and efficiency in maintenance works, increasing safety and well-being of the occupants, expanding the life of building stocks and expanding the value of investment for the government building assets. The maintenance practice in Malaysia is still emerging in comparison to many developed nations. The purpose of this study is to determine the current scenario of the building maintenance approach at the design stage in public buildings in Malaysia. Design/methodology/approach: An extensive questionnaire survey was held, involving 312 key players (38 per cent out of 820 predetermined participants) in Malaysia. Findings: The analysis showed that building maintenance in public building in Malaysia still uses the reactive approach. Despite the Malaysian Government's adoption of a proactive maintenance approach, unfortunately, there are some misunderstandings among the key players regarding the approach. The research results demonstrate that the key players had a lack of understanding on the concept of the proactive maintenance management approach and that they were either ignorant or had insufficient awareness of proactive maintenance approach. Originality/value: The contribution of this study is useful for the government to adopt a more proactive building maintenance policy at the design stage, to give awareness on proactive building maintenance to the key players in their construction project and as a guide to the key players to adopt a maintenance plan at the design stage of work.